2018
DOI: 10.14716/ijtech.v9i5.1266
|View full text |Cite
|
Sign up to set email alerts
|

An Anticorrosion Coating from Ball-milled Wood Charcoal and Titanium Dioxide using a Flame Spray Method

Abstract: In coating technology, many coating methods have been developed to enhance metal's resistance to corrosion. This study demonstrated the use of a simple, easy, and economical manual thermal flame spray method to create an anticorrosion coating layer composed of ballmilled wood charcoal (a readily-available source of carbon) and titanium dioxide (TiO2). The coating materials were sprayed and melted by passing them through a flame; they were then deposited onto the surface of metal substrate of structural steel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…X-ray analysis also revealed traces of augite -Ca [Mg, Fe 2+ , Al, Fe 3+ (Si, Al)2O6] (d = 1.41; 1.32; 1.07). Segregation is significant in the crystallization process because it accelerates under certain ideal conditions (Sycheva, 2016(Sycheva, , 2017(Sycheva, , 2019Sycheva & Poljakova, 2013Saraswati et al, 2018). Figure 4 shows delamination that occurred during the heat treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray analysis also revealed traces of augite -Ca [Mg, Fe 2+ , Al, Fe 3+ (Si, Al)2O6] (d = 1.41; 1.32; 1.07). Segregation is significant in the crystallization process because it accelerates under certain ideal conditions (Sycheva, 2016(Sycheva, , 2017(Sycheva, , 2019Sycheva & Poljakova, 2013Saraswati et al, 2018). Figure 4 shows delamination that occurred during the heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Steel structures in agricultural construction are subject to severe corrosion damage due to high concentrations of animal waste, high humidity, and ammonia-phosphate fertilizers used in agriculture. To strengthen the corrosion resistance of steel and the attractiveness of the metal surface, the quality of the relevant protective coatings must be improved (Saraswati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion cannot be stopped, but corrosion can be reduced and inhibited in various ways namely using corrosion inhibitors [7]. Cathodic protection [8], coating [9], and others. Recent developments have shown that the use of inhibitors is the most effective and efficient way to protect corrosion on metals [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that surface structure modification as surface hardening (Ismail and Taha, 2014) and coating deposition has been widely used to reduce part production costs (Luo et al, 2014), to improve wear resistance, hardness, or to act as environmental barrier coating (EBC) for critical components, resulting in higher oxidation or corrosion resistance (Singh et al, 2022). Thus, the selection of appropriate coating material and composition becomes particularly important (Saraswati, Nugroho, and Anwar, 2018). The FeCrAlY was receiving attractive attention for high-temperature oxidation and corrosion resistance applications because of the formation of a protective scale in the external layer (Wessel et al, 2004;Bennett and Bull, 1997).…”
Section: Introductionmentioning
confidence: 99%